(untitled) (Research, Society and Development, 2020)
The main cause of inefficiency in a construction site is directly related to the lack of planning and organization in relation to the whole set. Faced with this scenario, civil construction companies have been innovating their managerial concepts in their way of building, with adaptations of philosophies born in other branches of production, such as "Lean Production", adapted to the construction and thus originating the term "Lean Construction". A construction company is stronger competitively from the moment it provides more efficiency, economy and agility in its production system. In this context, this study aims to present the philosophy of Lean Construction being executed in a project in the city of Juazeiro do Norte from a case study, analyzing the aspects of planning through the use of lean construction tools that are able to avoid waste and rework, in addition to reducing costs. The accomplishment of this work is based, initially, on a bibliographic review on the subject and later a case study. The company presented difficulties and limitations when introducing new practices to the construction site, but some innovations with regard to precautions with rework or any anomaly that will generate financial physical damage in the work presented great relevance in the construction of the region. It is concluded that the company presented difficulties and limitations when introducing new practices to the construction site, motivated by the need for skilled labor.